Exploring problem focused vs emotion focused stress management: a qualitative study on tertiary institution students using in-depth interviews - Pawson, Megan (The IIE, 2020)
The purpose of this research is to determine whether student’s stress management is problem focused or emotion focused, as well as to determine if the current global pandemic has had an impact on the stress that students experience in their daily lives. Stress is seen as a prominent part in tertiary institution students’ lives, however, there is a lack of research on the impact that the pandemic might have on stress experienced by students. This study is qualitative in nature and made use of semi-structured in-depth interviews as a means of data collection to allow participants to share their own subjective experiences related to stress and the pandemic. The sample comprised of five participants who form part of the tertiary institution community ranging between first year students and honours level students, and who experience high levels of stress. More so, thematic analysis was used as a method for data analysis, which identified three themes: Description of stress, Determination of stress management, and Impact of the pandemic. Findings from this research suggested that students relied more on emotion focused stress management, and that the pandemic had a great impact on their academics and physical- and emotional well-being.
Keywords: Problem-focused stress management; Emotion-focused stress management; Tertiary education; Students